2020
DOI: 10.1101/2020.08.01.20166553
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mucosal versus systemic antibody responses to SARS-CoV-2 antigens in COVID-19 patients

Abstract: While the antibody response to SARS-CoV-2 has been extensively studied in blood, relatively little is known about the mucosal immune response and its relationship to systemic antibody levels. Since SARS-CoV-2 initially replicates in the upper airway, the antibody response in the oral cavity is likely an important parameter that influences the course of infection. We developed enzyme linked immunosorbent assays to detect IgA and IgG antibodies to the SARS-CoV-2 spike protein (full length trimer) and its recepto… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

53
293
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 228 publications
(350 citation statements)
references
References 50 publications
(77 reference statements)
53
293
3
Order By: Relevance
“…Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) emerged in late 2019 in China and caused a coronavirus disease 2019 (COVID- 19) pandemic. To mitigate the public health, economic and societal impacts of the virus, a vaccine is urgently needed.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) emerged in late 2019 in China and caused a coronavirus disease 2019 (COVID- 19) pandemic. To mitigate the public health, economic and societal impacts of the virus, a vaccine is urgently needed.…”
mentioning
confidence: 99%
“…The causative agent was identified as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), a betacoronavirus closely related to the SARS-CoV-1 from 2002-2004 2 . SARS-CoV-2 caused a sizable epidemic of coronavirus disease 2019 (COVID- 19) in China and then spread globally and caused a pandemic. Coronaviruses are enveloped viruses with a large, single stranded positive sense RNA genome.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Short immunity periods are the case for seasonal human coronaviruses (Callow et al, 1990;Galanti and Shaman, 2020;Kissler et al, 2020). Although natural infection with SARS-CoV-2 can induce neutralizing antibodies in humans (Brouwer et al, 2020;Chi et al, 2020;Ju et al, 2020;Shi R. et al, 2020), we still do not know if the infection confers immunity to prevent reinfection and, if so, for what duration (Altmann and Boyton, 2020;Ibarrondo et al, 2020;Isho et al, 2020;Kirkcaldy et al, 2020;Long et al, 2020;Robbiani et al, 2020;Staines et al, 2020). Many cases that tested positive after once turning negative are currently considered as reactivation, long-term shedding, or detection of residual genetic material Mahase, 2020b;Xiao A. T. et al, 2020) although a few cases of possible reinfection have been reported (Bloomberg, 2020).…”
Section: Coronaviruses Including Sars-cov-2mentioning
confidence: 99%